Strategi Komunikasi Pemasaran Agrowisata Paloh Naga Desa Denai Lama Kecamatan Pantai Labu Kabupaten Deli Serdang - Nona Halmiaty; Abdul Haris; Agung Suharyanto (Universitas Medan Area, 2023)
An effective communication strategy requires good planning with communication methods or tools for marketing activities. This study aims to determine the marketing communication strategy of Paloh Naga Agrotourism, Denai Lama Village, Pantai Labu District, Deli Serdang Regency. The type of method used in this research is descriptive qualitative. Data obtained from observations, interviews, and documentation using descriptive analysis techniques, namely describing the events studied. The results of this study indicate that in implementing the marketing communication strategy of Paloh Naga agrotourism in the village of Denai Lama, Pantai Labu District, Deli Serdang Regency, to attract tourists, there are five types of promotions or what is often referred to as the promotion mix, namely: (Advertising) by using advertisements such as brochures, signage, and online media such as Facebook and Instagram accounts; (Sales promotion) through managers and promotion and marketing staff providing information from social media accounts or through direct face-to-face interactions between entrepreneurs and consumers; Public Relations (Humas) in a way where the promotion and management staff of Agro-tourism Paloh Naga collaborate with various media parties with the aim of introducing Paloh Naga tourism and increasing the number of tourist visitors; (Personal selling) by means of promotional staff and managers informing visitors of the latest information about Paloh Naga agro-tourism; (Direct selling) is a way for traders to promote products or services that are displayed directly and involve direct contact sales to consumers.